Efficacy and safety of cariprazine in bipolar I depression: A double‐blind, placebo‐controlled phase 3 study. (6th November 2019) - Earley, Willie R.; Burgess, Maria V.; Khan, Barbara; Rekeda, Ludmyla; Suppes, Trisha; Tohen, Mauricio; Calabrese, Joseph R.
Abstract: Objective: To assess the efficacy, safety, and tolerability of cariprazine in the treatment of the depressed phase of bipolar I disorder in adults (NCT02670538 ). Methods: In this phase 3 double‐blind placebo‐controlled study, adult patients with bipolar I disorder according to the Diagnostic and Statistical Manual — 5th Edition criteria and a current depressive episode were randomized to placebo (n = 167), cariprazine 1.5 mg/day (n = 168) or cariprazine 3.0 mg/day (n = 158). Efficacy parameters were changes in the Montgomery‐Åsberg Depression Rating Scale (MADRS) total scores (primary) and Clinical Global Impressions — Severity (CGI‐S) scores (secondary) from baseline to Week 6 compared to placebo. A mixed‐model for repeated measures was used to estimate the least‐squares mean differences (LSMD); P ‐values were adjusted for multiplicity. Adverse events (AEs), laboratory results, vital signs, and suicide risk were monitored. Results: Cariprazine 1.5 mg/day significantly reduced depressive symptoms on the primary (MADRS LSMD = −2.5; adjusted P = .0417) and secondary (CGI‐S LSMD = −0.3; adjusted P = .0417) efficacy parameters vs placebo; differences were not statistically significant for cariprazine 3.0 mg/day. Common treatment‐emergent AEs (≥5% in either cariprazine group and at least twice the incidence of placebo) were akathisia, restlessness, nausea, and fatigue. Mean metabolic parameter changes were low and generally comparable among groups; mean weight increases were ≤0.5 kg for all groups. Conclusions: Cariprazine 1.5 mg/day significantly reduced depressive symptoms in adults with bipolar I depression compared to placebo, but differences were not significant for cariprazine 3.0 mg/day. The safety and tolerability profiles were similar to previous studies of cariprazine.